Synthesis of Tungsten Oxide Nanorod, Its Application on Textile Material, and Study of Its Functional Properties - Abdul Azeem; Munir Ashraf; Usman Munir; Zahid Sarwar; Sharjeel Abid; Naeem Iqbal (Journal of Nanotechnology)
Nanomaterial and its application in textiles are emerging as vast and diverse field due to enhanced functionalized characteristics. This study emphasizes the fabrication of tungsten trioxide nanostructured rods and analyzes its electrostatic and ultraviolet resistance properties. These nanorods are synthesized by hydrothermal method. Through hydrothermal method rod like nanostructures were grown on polyester fabric as it withstands curing temperature easily. The growth mechanism of the film is investigated. Electrostatic analysis of treated polyester fabric was failed but the analysis of seeded solution revealed that it has tunable transmittance modulation under different voltages and repetitive cyclic between the clear and blue states. Ultraviolet resistance of 100% seeded polyester fabric was higher than untreated fabric with respect to increasing concentration of nanorods. Results show that although the seeded solution is perfect, the conductivity of tungsten trioxide cannot be achieved on textiles.